The Nantauraka tradition of the Kaili people in the city of Palu and its Educational Values - Wasmi; Idrus A. Rore; Fajar Nugroho (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Adat Nantauraka is a local cultural ritual tradition that reflects the identity and self‑awareness of the Kaili ethnic community in Mamboro Village, Palu City. This tradition is carried out as a ritual to ward off disasters, as well as an expression of gratitude so that the community may be spared from calamities and disease outbreaks. Historically, this custom has been practiced from the late 18th century to the early 19th century and has continued to endure through acculturation between local customs and Islamic teachings. This study aims to describe the historical background, the performance procedures, and the educational values contained in the Adat Nantauraka. The research uses a qualitative method with a descriptive approach through observation, interviews, and documentation, and is analyzed through data reduction, data presentation, and conclusion drawing. The results show that the ritual is carried out in three stages: 10 Muharram, 23 Muharram, and its peak in the month of Rajab. This tradition embodies the meaning of self‑purification and environmental purification, as well as the hope of being spared from harm. The educational values it conveys include religiosity, togetherness, cooperation, social responsibility, discipline, adherence to norms, respect for ancestors, environmental concern, as well as reflection and self‑control